АДАБИЙ МАТН ВА МУСТАҚИЛ ФИКРЛАШ - Ниёзметова, Р.Х. (SCIENCE and SOCIETY, 2016)
The article deals with introductions of different kinds of work, ways of the preparation for critical thinking, even being provided with materials, for the full understanding the content of the literary text. Here are described the demonstration each other’s lacks in the group works and gradual, easy overcoming of some lexical and grammatical errors in teaching students.